1990
DOI: 10.1288/00005537-199002000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Fourth branchial pouch sinus: Principles of diagnosis and management

Abstract: The fourth branchial pouch sinus is a congenital anomaly which most frequently manifests itself by recurrent episodes of neck abscess or acute suppurative thyroiditis. This lesion usually becomes symptomatic before the age of 10 years and is more common than has previously been suspected. It has been found on the left side in 93% of the 28 cases reported in the English literature. Barium swallow during periods of quiescence and nasopharyngoscopy have frequently been successful in identifying the presence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…The classic description is based on an understanding of the segmental branchial anatomy and involves persistence of the pharyngobranchial duct, which connects the third and fourth pharyngeal pouches to the pharynx and normally degenerates during the seventh week of development. Persistence of this duct results in a sinus tract that communicates with the pyriform fossa, representing persistence of both branchial cleft and corresponding pouch [1, 2]. …”
Section: Discussionmentioning
confidence: 99%
“…The classic description is based on an understanding of the segmental branchial anatomy and involves persistence of the pharyngobranchial duct, which connects the third and fourth pharyngeal pouches to the pharynx and normally degenerates during the seventh week of development. Persistence of this duct results in a sinus tract that communicates with the pyriform fossa, representing persistence of both branchial cleft and corresponding pouch [1, 2]. …”
Section: Discussionmentioning
confidence: 99%
“…Then it passes between the thyroid and cricoid cartilages and opens in to the pyriform fossa. According to Godin et al [17], almost all the fourth arch anomalies reported occurred in the left side. In our series also, the fourth arch fistula occurred in the left side.…”
Section: Individual Branchial Anomaliesmentioning
confidence: 99%
“…For the recurrent infections and unclear anatomy, it is difficult to reveal the whole sinus. Methylene blue, microscope guidance, probe guidance, nelaton catheter, and Fogarty catheter can be used to help exposure [2125]. In this study, 5 patients (100%) successfully underwent complete excision of fistula, and 2 patients (40%) simultaneously underwent ipsilateral gland resection.…”
Section: Discussionmentioning
confidence: 91%